Facile extraction of chitin and chitosan from shrimp shell - Hisham, Firzanah; Mohd Hatta, Maziati Akmal; Ahmad, Farah; Ahmad, Kartini (Elsevier Ltd, 2021)
In this study, the chitin and chitosan were extracted from shrimp shell through two-steps acid and alkaline treatment. The shrimp shell was deproteinized by 1 Mof sodium hydroxide and demineralised by 1%, 2%, 3%, 4% and 5% of hydrochloric acid, respectively. The produced chitin was characterized by FTIR and FESEM. FTIR depicted that the chitin extracted from shrimp shell was in a-chitin isomorph. The surface morphology of chitin was found to increase with an increase in acid concentration. The chitosan film with rod-like micro-structure was produced when dissolved in 2% of acetic acid. It was shown that chitosan with 65% of DD was successfully produced using this chemical route.